China in Africa: Plunder or Co-Development - Spitz, Dominic (2008)
This paper analyzes the impact of the emergence of China, as an important player in the global economy, on various African economies. China's rising economic activity in Africa has brought much attention to the increasing trade and investment relations between both. China's increased presence on the African continent is explained both by: its constant need to find a secure and sustainable supply of raw materials and its need to find markets capable of serving its industrial output, through exports. The aim of this study is therefore to examine whether China's activities in Africa will stimulate Africa's economic growth without compromising the development of Africa itself. We will discuss the economic opportunities of the Sino-African venture as well as the political and social impacts caused by this partnership.